Theoretical Study: Implementation of The Integrated Model In Islamic Religious Education Learning - Danang Dwi Prasetyo (SALIHA: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to examine theoretically the implementation of the integrated model in learning Islamic Religious Education. This type of research is library research with a descriptive approach, the primary data source is a book entitled How To Integrate The Curricula Third Edition, by Robin Fogarty Foreword By Heidi Hayes Jacobs, published in California by Corwin A SAGE Company in 2009. The technique of analysis is content analysis. The result of the research is the implementation of an integrated model in PAI learning through three steps, namely the educator's step of designing a learning plan program by determining KD, determining the results. The second step is the implementation stage, at this stage the educator carries out three activities, namely opening, core and closing. The third step is the culmination by conducting an assessment through tests on students.